2017
DOI: 10.1016/j.molcel.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Free Guanidine in Bacteria Is Regulated by a Widespread Riboswitch Class

Abstract: SUMMARY The guanidyl moiety is a component of fundamental metabolites including the amino acid arginine, the energy carrier creatine, and the nucleobase guanine. Curiously, reports regarding the importance of free guanidine in biology are sparse and no biological receptors that specifically recognize this compound have been previously identified. We report that many members of the ykkC motif RNA, the longest-unresolved riboswitch candidate, naturally sense and respond to guanidine. This RNA is found throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
369
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(388 citation statements)
references
References 54 publications
(71 reference statements)
15
369
0
Order By: Relevance
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
“…Three additional ligand specificity changes are suspected. Namely, some molybdenum cofactor riboswitches appear to exploit an altered aptamer structure to selectively recognize tungsten cofactor (20), certain flavin mononucleotide (FMN) riboswitches carry binding site mutations that alter ligand specificity (21,22), and a large number of guanidine-I riboswitches carry mutations in the binding pocket and sense an as-yet-unknown ligand (6).…”
mentioning
confidence: 99%
“…They also investigated a transporter (a SugE protein) in Clostridiales controlled by the guanidine-I riboswitch. They found that intrinsic fluorescence of tryptophan residues increases in a guanidine-dependent manner (K d ~1 mM), providing preliminary evidence that this transporter specifically recognizes guanidine (Nelson et al, 2016). …”
Section: Introductionmentioning
confidence: 95%
“…Ligand identification has proven elusive due to the wide variety of poorly studied genes under its control (Meyer et al, 2011). Nelson et al recently demonstrated that guanidine is the ykkC ligand (Nelson et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation